Pediatric integrative medicine: pediatrics' newest subspecialty? - Vohra Sunita; Surette Soleil; Mittra Deepika; Rosen Lawrence D; Gardiner Paula; Kemper Kathi J (BMC, 2012)
Abstract Background Integrative medicine is defined as relationship-centered care that focuses on the whole person, is informed by evidence, and makes use of all appropriate therapeutic approaches, healthcare professionals and disciplines to achieve optimal health and healing, including evidence-based complementary and alternative medicine. Pediatric integrative medicine (PIM) develops and promotes this approach within the field of pediatrics. We conducted a survey to identify and describe PIM programs within academic children's hospitals across North America. Key barriers and opportunities were identified for the growth and development of academic PIM initiatives in the US and Canada. Methods Academic PIM programs were identified by email and eligible for inclusion if they had each of educational, clinical, and research activities. Program directors were interviewed by telephone regarding their clinical, research, educational, and operational aspects. Results Sixteen programs were included. Most (75%) programs provided both inpatient and outpatient services. Seven programs operated with less than 1 FTE clinical personnel. Credentialing of complementary and alternative medicine (CAM) providers varied substantially across the programs and between inpatient and outpatient services. Almost all (94%) programs offered educational opportunities for residents in pediatrics and/or family medicine. One fifth (20%) of the educational programs were mandatory for medical students. Research was conducted in a range of topics, but half of the programs reported lack of research funding and/or time. Thirty-one percent of the programs relied on fee-for-service income. Conclusions Pediatric integrative medicine is emerging as a new subspecialty to better help address 21st century patient concerns.